2012
DOI: 10.1002/crat.201100643
|View full text |Cite
|
Sign up to set email alerts
|

Determination of optical parameters of Ga0.75In0.25Se layered crystals

Abstract: The optical properties of the Ga 0.75 In 0.25 Se crystals have been investigated by means of transmission and reflection measurements in the wavelength range of 380−1100 nm. The analysis of the results performed at room temperature revealed the presence of optical indirect transtions with band gap energy of 1.89 eV. The variation of the band gap energy as a function of temperature was also studied in the temperature range of 10−300 K. The rate of change of band gap energy (γ = −6.2 × 10 −4 eV/K) and absolute z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Due to interesting semiconductor properties, GaSe is used in microelectronic and epitaxial technologies (Emery et al, 1992;Rudolph et al, 2005;Ho et al, 2006;Huang et al, 2010;Late et al, 2012). The pronounced layered crystal structure of GaSe, space group P6m2, where dense atomic layers are linked by relatively weak van der Waals forces, defines many specific physical and chemical properties of GaSe, such as high anisotropy of mechanical, thermal, linear and nonlinear optical parameters, higher dop- (Cenzual et al, 1991;Fernelius, 1994;Singh et al, 1998;Abdullaev et al, 2002;Andreev et al, 2006;Feng et al, 2008;Abdinov et al, 2010;Sarkisov et al, 2010;Zhang et al, 2011;Isik & Gasanly, 2012;Atuchin et al, 2013a,b ;Kato et al, 2013). The weak interlayer chemical bonds in the GaSe structure results in low mechanical properties and high GaSe crystal cleavage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to interesting semiconductor properties, GaSe is used in microelectronic and epitaxial technologies (Emery et al, 1992;Rudolph et al, 2005;Ho et al, 2006;Huang et al, 2010;Late et al, 2012). The pronounced layered crystal structure of GaSe, space group P6m2, where dense atomic layers are linked by relatively weak van der Waals forces, defines many specific physical and chemical properties of GaSe, such as high anisotropy of mechanical, thermal, linear and nonlinear optical parameters, higher dop- (Cenzual et al, 1991;Fernelius, 1994;Singh et al, 1998;Abdullaev et al, 2002;Andreev et al, 2006;Feng et al, 2008;Abdinov et al, 2010;Sarkisov et al, 2010;Zhang et al, 2011;Isik & Gasanly, 2012;Atuchin et al, 2013a,b ;Kato et al, 2013). The weak interlayer chemical bonds in the GaSe structure results in low mechanical properties and high GaSe crystal cleavage.…”
Section: Introductionmentioning
confidence: 99%
“…The weak interlayer chemical bonds in the GaSe structure results in low mechanical properties and high GaSe crystal cleavage. This provides a possibility to prepare the large area (001) crystal surface by a simple cleavage technique, and the cleaved surface commonly possesses optical quality and atomic level flatness (Fernelius, 1994;Sarkisov et al, 2010;Borisenko et al, 2011;Isik & Gasanly, 2012;Atuchin et al, 2013a,b;Guo et al, 2013b;Ni et al, 2013). It should be pointed that the cleaved GaSe(001) surface shows specifically high chemical inertness in the air under normal conditions similar to several other layered chalcogenides (Tambo & Tatsuyama, 1985;Atuchin et al, 2011;Yashina et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The optical characterization analysis on Ga x In 1−x Se indicated that band gap energy increases from 1.2 eV (x = 0, InSe) to 2.0 eV (x = 1, GaSe) [15]. Our research group reported studies on the characterization of Ga 0.75 In 0.25 Se (x = 0.75) crystals by means of optical absorption [16], ellipsometry [17], and dark electrical resistivity [18]. Moreover, in our previous work, we have reported optical properties of the thermally evaporated as-grown and annealed GIS thin films [19].…”
Section: Introductionmentioning
confidence: 99%
“…The cleavage plane of the GaSe:InS crystal was found to be orthogonal to the growth direction that is quite a rare event for layered chalcogenide compounds. [5][6][7][8][10][11][12][13]20,[24][25][26][27][28] Due to such orientation of the cleavage plane, the crystal was broken into several 15-30 mm pieces during cooling. A view through the cleaved faces of one such piece is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%